DESCRIPTION OF HIV KNOWLEDGE AMONG PREGNANT WOMEN ACCORDING TO DEMOGRAPHIC CHARACTERISTICS - Elyana Awalia Subagya; Witdiawati Witdiawati; Ema Arum Rukmasari (Journal of Maternity Care and Reproductive Health, 2026)
Human Immunodeficiency Virus (HIV) remains a global public health issue, including among pregnant women who are at risk of transmitting the infection to their fetuses. Knowledge is one of the factors influencing pregnant women’s behavior regarding early detection as a preventive measure against mother-to-child HIV transmission. The purpose of this study is to identify the level of knowledge among pregnant women regarding HIV transmission and prevention. This study employed a descriptive quantitative design. The sample was selected using total sampling from 100 pregnant women. The research instrument was the HIV Knowledge Questionnaire-18 (HIV-KQ-18) in the Indonesian language. Data were analyzed using univariate analysis. The results of the study indicate that the majority of pregnant women (52%) have insufficient knowledge regarding HIV transmission and prevention; this was particularly common among respondents aged 20–35 years, those who were unemployed, had a secondary education, were in their second trimester of pregnancy, had given birth to one child, and had received information related to HIV. These findings highlight the need for strengthened structured HIV education within antenatal care services. Further research is recommended to analyze the determinants influencing knowledge levels and to explore the relationship between knowledge and VCT behavior among pregnant women.